Alternative Substitution for Mortar Paste - Khairul Hisyam, Nur Alya Natasha; Wan Mohamad Noor, Wan Nur Hazirah; Muhamad Aqmarr Norhakim, Nurul Nargiss Najwa; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2025)
This research aims to assess the impact of partial substitution in mortar mix on mechanical properties and durability. The study involves the use of alternative materials (PET) replacing a portion of the conventional cement and sand in mortar. Examination includes compressive strength testing, water absorption measurements, and steel reinforcement tests on mortars with varying substitution percentages. Results indicate that mortars with specific substitution ratios exhibit satisfactory performance in compressive strength and water absorption while maintaining durability characteristics. The implications of this study's findings can contribute to the development of more sustainable and high-durability mortar mixes for use in building construction.